Strategický rozvoj mikroregionu Pod Chlumem - Flanderka, Michal (Univerzita Pardubice, 2006)
Tato diplomová práce se zabývá problematikou regionálního rozvoje v ČR, strategického plánování a rozvoje mikroregionů. Cílem této práce je analýza a zhodnocení stávajícího stavu mikroregionu Pod Chlumem, charakteristika jeho strategického plánu včetně jeho zhodnocení, určení hlavních směrů a doporučení úspěšného rozvoje tohoto mikroregionu v oblasti cestovního ruchu. Formálně se diplomová práce dělí do sedmi hlavních částí. První dvě části teoreticky řeší vybranou problematiku. První část tak stručně charakterizuje regionální rozvoj v České republice. Druhá část se věnuje strategickému plánování, konkrétně obecné tvorbě strategického plánu mikroregionu. Zbylých pět částí je zaměřeno na vybranou problematiku již z praktického hlediska. V těchto částech je proto charakterizován a analyzován mikroregion Pod Chlumem a jeho strategický plán. Podstatu těchto částí ale určitě tvoří navržení dvou projektových záměrů, které by přispěly k rozvoji cestovního ruchu v mikroregionu.

This thesis deals with the problem of regional development in the Czech Republic, strategic planning and the development of microregions. The aim of my thesis is to analyse and assess the current state of the microregion Pod Chlumem, and to characterise its strategic plan including its assessment and establishing the main ways towards prosperous development of this microregion in the field of tourist industry. Formally is my thesis divided into seven main parts. The first two theoretically deal with the chosen topic. The first part briefly characterises regional development in the Czech Republic whereas the second part focuses on strategic planning, concretely on the general creation of a strategic plan of a microregion. The five remaining chapters deal with the chosen topic from a more practical point of view. Therefore the microregion Pod Chlumem with its strategic plan is analysed and characterised here. Without question, the designing of the two project propositions which would help to the development of travel industry in the microregion, makes the essence of the last five parts.
Strategical development of the Microregion Pod Chlumem
Keywords: regional developments; Strategic Planning; microregions; regionální rozvoje; strategické plánování; mikroregiony; Pod Chlumem